Method for Determining the Susceptibility of the Track - Jerzy Kisilowski; Rafał Kowalik (Applied Sciences, 2022)
This paper discusses real-world experiments in which selected ground imperfections were dynamically analysed in terms of track susceptibility for a linear and non-linear system. The imperfections included wheel pressure on local ground irregularities within the railway turnout. In this study, susceptibility was assumed as an element between two points (two masses)—most often susceptibility is assumed as a Voigt model (parallel combination of stiffness and damping). The tests were carried out for two configurations of train passage through a railway turnout on straight and diverging track. The track stiffness parameters of the railway turnout were determined from deflection measurements measured by sensors positioned at different points of the turnout. The components of the railway turnout were loaded with different forces. The damping parameter was determined from bench measurements of the actual track component. The function describing this damping is dry friction and such a function was determined. The second part of the study was concerned with measurements of stiffness and moments of inertia in a railway switchyard. The analysis carried out indicated the significance of the adverse effects of selected factors on the operation of the railway track (e.g., increasing the length of non-contact of the track with the ground or additional deflections of the railway track rail arising). The paper points out that such imperfections, in addition to the calculated additional deflections, cause, among other things, disturbances in the progressive movement of the rolling stock.